DLC1 suppresses NF-κB activity in prostate cancer cells due to its stabilizing effect on adherens junctions - Tripathi, Veenu (Springer International Publishing, 2014)
DLC1 (Deleted in Liver Cancer 1) gene encodes a RhoGTPase-activating protein (RhoGAP), which exerts most of its tumor suppressor functions through suppression of small Rho GTPases proteins RhoA, RhoB, RhoC and to some degree Cdc42, but not Rac. RhoGTPases are implicated in NF-κB activation in highly invasive prostate carcinoma (PCA), with consequences on cell proliferation, survival and metastatic capacity. Here we demonstrate that DLC1 transduction in two androgen-independent (AI) and highly metastatic PCA cell lines negatively regulates NF-κB activity in a GAP- and α-catenin-dependent manner. Expressed DLC1 protein suppresses the phosphorylation of NF-κB inhibitor, IκBα, causes its relocation from membrane ruffles into cytoplasm and attenuates its ubiquitination and subsequent degradation. DLC1-mediated NF-kB suppression and its effects are comparable to NF-κB inhibition using either shRNA knockdown or peptide inhibitor. Expression of transduced DLC1 suppressed the expression of NF-κB mediated genes. Such effects were found to be reliant on presence of calcium, indicating that the observed modifications are dependent on, and enabled by DLC-mediated stabilization of adherens junctions. These results expand the multitude of DLC1 interactions with other genes that modulate its oncosuppressive function, and may have potential therapeutic implications.